2005
DOI: 10.1189/jlb.0205083
|View full text |Cite
|
Sign up to set email alerts
|

The interferon-inducible gene, Ifi204, is transcriptionally activated in response to M-CSF, and its expression favors macrophage differentiation in myeloid progenitor cells

Abstract: The interferon-inducible (Ifi)204 gene was isolated as a macrophage-colony stimulating factor (M-CSF)-responsive gene using a gene trap approach in the myeloid interleukin-3 (IL-3)-dependent FD-Fms cell line, which differentiates in macrophages in response to M-CSF. Here, we show that Ifi204 was transcriptionally activated in response to M-CSF, and FD-Fms cells decreased their growth and committed toward a macrophage morphology; this induction was abrogated when the differentiation signal of the M-CSF receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…The p204 gene was isolated as a macrophage-colony-stimulating factor (M-CSF)-responsive gene by using a gene trap approach in the interleukin (IL)-3-dependent myeloid FD-Fms cell line. Moreover forced expression of p204 strongly repressed the IL-3 and M-CSF-dependent proliferation, whereas it promoted the M-CSF-induced macrophage differentiation of FD-Fms cells (Dauffy et al, 2006). p204 may also play an important role in lymphocytic differentiation based on the observation that p204 mRNA levels are higher in less mature double-positive (CD4 ϩ CD8 ϩ ) thymocytes than in single-positive (CD4 ϩ or CD8ϩ) thymocytes (Deftos et al, 2000).…”
Section: © 2008 By the American Society For Cell Biology 2113mentioning
confidence: 99%
See 1 more Smart Citation
“…The p204 gene was isolated as a macrophage-colony-stimulating factor (M-CSF)-responsive gene by using a gene trap approach in the interleukin (IL)-3-dependent myeloid FD-Fms cell line. Moreover forced expression of p204 strongly repressed the IL-3 and M-CSF-dependent proliferation, whereas it promoted the M-CSF-induced macrophage differentiation of FD-Fms cells (Dauffy et al, 2006). p204 may also play an important role in lymphocytic differentiation based on the observation that p204 mRNA levels are higher in less mature double-positive (CD4 ϩ CD8 ϩ ) thymocytes than in single-positive (CD4 ϩ or CD8ϩ) thymocytes (Deftos et al, 2000).…”
Section: © 2008 By the American Society For Cell Biology 2113mentioning
confidence: 99%
“…This is due at least in part to the binding of p204 to the Id proteins, including Id1, Id2, and Id3, and overcoming the inhibition by the Id proteins of MyoD activity in skeletal muscle differentiation, and Gata4 and Nkx2.5 activity in cardiac myocyte formation (Liu et al, 2002;Ding et al, 2006b). A recent publication revealed the involvement of p204 also in macrophage differentiation (Dauffy et al, 2006). The p204 gene was isolated as a macrophage-colony-stimulating factor (M-CSF)-responsive gene by using a gene trap approach in the interleukin (IL)-3-dependent myeloid FD-Fms cell line.…”
mentioning
confidence: 99%
“…4A). These include DUSP5, a negative-feedback regulator of Erk1/2, which inhibits macrophage differentiation and favors granulocytic differentiation (Grasset et al 2010), interferon-inducible gene 204 (Ifi204), which suppresses proliferation and favors differentiation (Dauffy et al 2006), and the adaptor proteins suppressor of cytokine signaling 1 (Socs1) and SKAP55-related (SKAP55R). Socs1 associates with CSF-1R pTyr-697 and pTyr721 binding sites to inhibit proliferation by an unknown mechanism (Bourette et al 2001).…”
Section: Er Stanley and V Chitumentioning
confidence: 99%
“…12,14,15,[19][20][21][22][23][24] The current study sought to elucidate the role of p204 in chondrogenesis, with the special focus on chondrocyte hypertrophy, and the molecular events underlying this process. p204 demonstrated prominent expression in the growth plate prehypertrophic and hypertrophic chondrocytes ( Figure 1) and was found to be induced in the course of chondrocyte differentiation in vitro (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, forced expression of p204 strongly repressed the IL-3-and M-CSF-dependent proliferation, whereas it promoted the M-CSF-induced macrophage differentiation of FD-Fms cells. 23 We previously reported that p204 acted as a transcriptional coactivator of Cbfa1 and therefore enhanced osteoblast differentiation 12 and that pRb is an essential linker between p204 and Cbfa1 thereby increasing its activity; 24 p204, pRb, Cbfa1 and Ids form a protein interaction network and act in concert in regulating the differentiation of pluripotent C2C12 to osteoblasts. 25 In this study, we describe the expression and function of p204 in hypertrophic chondrocyte differentiation as well as the molecular mechanism involved.…”
mentioning
confidence: 99%